Coming Out of the Closet in Japan: An Exploratory Sociological Study. Issue 5 (20th October 2018) - Tamagawa, Masami
ABSTRACT: Invisibility is a major obstacle to the improvement of the lives of GLBT individuals in contemporary Japanese society. Japanese GLBT scholars and activists attest that it is extremely difficult to come out of the closet in Japan. There is little systematic research, however, as to why. Using online survey data from 136 GLBT individuals in Japan, this article examines some of the reasons Japanese GLBT individuals cannot come out, especially to their parents. A coming-out experience score was created to assess the difficulty or favorability of various coming-out experiences. The data suggest that: (1) the majority of Japanese individuals consider coming out a desirable choice; (2) it is considerably more difficult to come out to parents than to coworkers or schoolmates; (3) between parents, although it is considered more difficult to come out to a father than to a mother, the experience of coming out to a mother is significantly less favorable than the experience of coming out to a father; and (4) coming out to coworkers and schoolmates are only relatively easy. The findings are discussed in the context of various sociocultural configurations, including patriarchy, heteronormativity, and GLBT in popular culture, and homophobia in contemporary Japanese society.